Effects of Vibrio harveyi on plasma clotting protein (coagulogen) of white shrimp Litopenaeus vannamei. (18th May 2015) - Chuang, Wen‐Hsiao; Liu, Ping‐Chung; Chien, Yu‐Chun; Wu, Yu‐Chen; Lee, Kuo‐Kau
Abstract: Blood clotting exhibits various important functions, including the prevention of body fluid loss and invasion of pathogens in shrimp. The effects of pathogenic Vibrio harveyi on plasma of white shrimp ( Litopenaeus vannamei ) in vitro and in vivo were investigated in this study. The clotting protein (coagulogen) in plasma of white shrimp pre‐incubated with extracellular products (ECP) of V. harveyi was found apparently decreased and fast‐migrated in crossed immunoelectrophoresis (CIE) gels. In addition, the coagulogen had been degraded to many low molecular‐weight protein bands in plasma pre‐incubated with ECP on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) gels. When pre‐challenged with bacterial cells and ECP of V. harveyi, the white shrimp began to die at about 30 and 16 h respectively. Moreover, plasma coagulogen was decreased more obvious in shrimp challenged with ECP than that with bacterial cells as visualized in CIE gels, and total plasma protein in both group of shrimp were all decreased. Haemolymph withdrawn from moribund shrimp pre‐challenged with V. harveyi or its ECP was observed unclottable. However, the addition of clotting factors (transglutaminase and/or Ca 2+ ) to these unclottable plasma could apparently promote their re‐clotting ability as jelly‐like solid observed in microtubes. The recovery of clotting ability of plasma from moribund shrimp was due to the reformation of coagulogen (200 kDa) after adding the two clotting factors as shown on CIE and SDS‐PAGE gels. The present results suggest that the infection of V. harveyi in white shrimp may not only degrade coagulogen but also influence the presence of transglutaminase and Ca 2+ ion.